2014
DOI: 10.5115/acb.2014.47.4.244
|View full text |Cite|
|
Sign up to set email alerts
|

Stable isotope analysis of Joseon people skeletons from the cemeteries of Old Seoul City, the capital of Joseon Dynasty

Abstract: Stable carbon and nitrogen isotope analysis reveals the diets of different human populations in history. In this study, we performed stable isotope analysis on human skeletons from Joseon-period cemeteries discovered around Old Seoul City (Hansung). Our data clearly showed that Joseon individuals consumed more C3-based than C4-based foods as the main staples, and that the proteins they ate were mainly of terrestrial, but not of marine origin. Stable isotope values exhibited unique patterns in each of our sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The δ 13 C value for the Silla individual examined in the present study was -19.72 ± 0.12‰, indicating that she had consumed a more C 3 -based diet. In fact, this δ 13 C data is similar to the results of studies on Joseon skeletons [ 25 27 ], and slightly higher than those for ancient skeletons from Yeanri [ 14 ], Imdang [ 23 ], and Neukdo [ 24 ]. On the other hand, the present δ 15 N value (7.89 ± 0.38‰) is markedly lower than the data on any of the ancient or medieval skeletal remains discovered in South Korea.…”
Section: Discussionsupporting
confidence: 86%
“…The δ 13 C value for the Silla individual examined in the present study was -19.72 ± 0.12‰, indicating that she had consumed a more C 3 -based diet. In fact, this δ 13 C data is similar to the results of studies on Joseon skeletons [ 25 27 ], and slightly higher than those for ancient skeletons from Yeanri [ 14 ], Imdang [ 23 ], and Neukdo [ 24 ]. On the other hand, the present δ 15 N value (7.89 ± 0.38‰) is markedly lower than the data on any of the ancient or medieval skeletal remains discovered in South Korea.…”
Section: Discussionsupporting
confidence: 86%
“…Joseon people relied for their subsistence mainly on farming of rice and other grains. According to a previous stable-isotope analysis of Joseon skeletons (Yu et al, 2014), they mostly consumed C3-based foods as the main staples, and the proteins that they ate were mainly of terrestrial origin (only a few were of marine origin). Recently, in a stable-isotope comparison of archaeologically obtained hairs from Russian settlers (n = 13) and Joseondynasty people (n = 13), we revealed that the diet of Russian settlers had lower δ 13 C (mean = -21.92‰) and higher δ 15 N (mean = 12.16‰) values, compared with the Joseon people (mean = -19.65‰ for δ 13 C; mean = 11.47‰ for δ 15 N (Kim et al, 2023)).…”
Section: Discussionmentioning
confidence: 99%